PENARIKAN KEMBALI HARTA HIBAH SEBAGAI HARTA WARIS MENURUT KHI DAN KUHPERDATA - Putri, Rizqi Saniyyah; Ruslie, Ahmad Sholikhin (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Grants can be given to whoever the grantor wants, a grant is the voluntary and unrewarded giving of an object from someone to another person who is still alive to own it. Even though a grant can be given to anyone, the grant cannot be withdrawn except for a parent's gift to their child, this is contained in article 211 KHI, this is withdrawn because the adopted child receives threats from the parents because the gift assets that have been given are withdrawn and used as an inheritance to be given to his biological children. This type of research uses normative juridical with a statutory or conceptual approach It discusses (1) concept of withdrawing a grant, (2) comparisons between khi and the civil law regarding grants. The type of research used in writing this proposal is a type of normative law research. or normative juridical, one of the reasons for the transfer of property rights in the view of Civil Law and Islamic Law is through "Grants". By donating an object or item to another person, it means that something comes out of the owner who gave the gift and becomes the property of the person or legal entity that receives the grant. Thus, besides having a function and role as a transfer of power, this grant also has legal consequences and certain conditions, both according to Civil Law and Islamic Law. Therefore, grants are a means of solidarity among people, so all parties are expected not to manipulate grants that can deviate from their goals